Exploring the Impact of Complex Trauma on Individual Identity: Implementation of Strength-Based Cognitive Behavioral Therapy and Trauma-Informed Care - Septinda Rima Dewanti; Yuejiao Wu; Septinda Rima Dewanti; Yuejiao Wu (Universitas Negeri Malang, 2026)
This article presents an explanation of the relationship between individual culture and how individuals perceive complex trauma. This study examined the effect of neglect and rejection trauma on adolescent identity development under the influence of culture. A single-case study was employed to explore the impact of complex trauma on the subject. The subject of this study was a university student identified as a Muslim and Javanese. Data were collected from ten counselling interviews using Strength-Based Cognitive Behavioural Therapy and Trauma-Informed Care. The counselling interview transcriptions were analysed using reflexive thematic analysis. Themes in the data explain that complex trauma has caused the subject to experience identity confusion, and culture strongly influences the subject's attitudes toward traumatic experiences, especially in how she sees herself as a daughter of a Javanese family. Further, the result suggests the importance of considering virtues and values from the client's background to enhance client resilience during counselling.